Technical evaluation of available residual biomass in Colombia for its thermochemical conversion in fluidized bed reactors (2018)
In the present work, the results obtained from the physical, fluid dynamic and thermochemical characterization of available Colombian residual biomasses are reported. These biomasses were identified through the assessment of their technical energy potential. Data and analysis presented here have the potential to be the used as basis for further research aiming to the design, modeling and optimization of fluidized bed reactors for thermochemical conversion of residual biomass. In this way, the present thesis allows recognizing interesting residual biomasses in Colombia and defining the technical conditions at which they can efficiently be transformed to valuable products through thermochemical processes in fluidized bed reactors. Besides its technical character, the present work complements previous gasification and pyrolysis studies made in the research group on Biomass and Optimization of Thermal Processes – BIOT of the Universidad Nacional de Colombia. The use of residual biomass in fluidized beds in Colombia represents a valuable, renewable and clean option to produce power and/or fuels (also decentralized), and hence, to stimulate social, environmental and economic development in the country.